Significance of the surgical hepatic resection margin in patients with a single hepatocellular carcinoma. Issue 1 (25th October 2019) - Aoki, T; Kubota, K; Hasegawa, K; Kubo, S; Izumi, N; Kokudo, N; Sakamoto, M; Shiina, S; Takayama, T; Nakashima, O; Matsuyama, Y; Murakami, T; et al.
Abstract: Background: The impact of a wide surgical margin on the outcome of patients with hepatocellular carcinoma (HCC) has not been evaluated in relation to the type of liver resection performed, anatomical or non-anatomical. The aim of this study was to evaluate the impact of surgical margin status on outcomes in patients undergoing anatomical or non-anatomical resection for solitary HCC. Methods: Data from patients with solitary HCC who had undergone non-anatomical partial resection (Hr0 group) or anatomical resection of one Couinaud segment (HrS group) between 2000 and 2007 were extracted from a nationwide survey database in Japan. Overall and recurrence-free survival associated with the surgical margin status and width were evaluated in the two groups. Results: A total of 4457 patients were included in the Hr0 group and 3507 in the HrS group. A microscopically positive surgical margin was associated with poor overall survival in both groups. A negative but 0-mm surgical margin was associated with poorer overall and recurrence-free survival than a wider margin only in the Hr0 group. In the HrS group, the width of the surgical margin was not associated with patient outcome. Conclusion: Anatomical resection with a negative 0-mm surgical margin may be acceptable. Non-anatomical resection with a negative 0-mm margin was associated with a less favourable survival outcome. Graphical Abstract: Data of patients in Japan with hepatocellular carcinoma who had undergone a non-anatomical or anatomical resection were extracted from a nationwide survey database. A microscopically positive margin was associated with poorer overall survival. The outcome of patients with a negative but 0-mm margin was poor only in the non-anatomical resection group, suggesting that anatomical resection with a negative 0-mm margin is acceptable. Difference between anatomic and non-anatomic resection